Advancing Binaural Cochlear Implant Technology - Dietz, Mathias (Trends Hear, 2015)
This special issue contains a collection of 13 papers highlighting the collaborative research and engineering project entitled Advancing Binaural Cochlear Implant Technology—ABCIT—as well as research spin-offs from the project. In this introductory editorial, a brief history of the project is provided, alongside an overview of the studies.